The Accountant's Responsibility in Historical Perspective. - Brief, Richard P. (The Accounting Review, 1975)
Abstract One way to gain insight into the vexing and unsettled questions connected with the responsibility of accountants is to approach the subject from an historical perspective. In this article, the author examines nineteenth and early twentieth century thought on various topics which have been, and continue to be, of concern to accountants. It will become evident that history repeats itself and that most of the basic problems considered by accountants now are also those which have perplexed the profession for nearly a century. Thus despite all the changes in the business environment, controversy within the accounting profession today has remarkable similarities to the discussion taking place decades ago, as of April 1975. The article is divided into three sections. The first surveys accounting thought on the subjects of disclosure and alternative techniques and questions concerning the scope of audit and audit certificate. In the second section, the attitude toward the accountant's responsibility for forecasts and estimates is examined. The third section concludes that the emphasis on the past rather than the future conflicts with the idea of profit as a return for risk bearing.